Strategi Gerakan Komunitas Save Street Child Dalam Advokasi Perlindungan Hak Anak Jalanan Di Kota Surabaya - Iqbal Baihaqi, Mukhdlor (Jurnal Nawala Politika, 2017)
Social movement emerged as one of the phenomena in the era of modernity, there are several reasons that led to a prominent social movement in that era: The sense of alienation that raises the desire for community with solidarity and togetherness, the cheapness of social inequality and the transformation of the political system that opens up opportunities for collective action. A special study to find out the strategy of Save Street Child Surabaya community in achieving its goals. This study uses. And strategy. The method used in this research is descriptive qualitative, Unit analaisis from this research that is Strategy of Community Save child street Surabaya, Technique data of data based on: Primary data (observation, interview) and secondary data (literature study, Documentation). The results of the research are as follows: SSCS has a strategy in their movement to advocate its Vision, their advocacy is to attract street children to join SSCS, they offer several activities programs that aim to give children the rights they can, then advocate assistance from various parties, both government, private and other NGOs to support their programs. Keyword: Save Street Child Surabaya; Social movement, Strategy.